Cyclic AMP-induced slow inward current: its synaptic manifestation in Aplysia neurons - Kehoe, J (J Neurosci, 1990)
Three presynaptic neurons, monosynaptically connected to the medial cells of the pleural ganglion of Aplysia californica and previously shown to elicit cAMP-mediated diminutions in K conductance in those cells (Kehoe, 1985a, b), were shown to elicit still another slow synaptic current that resembles the cAMP-induced cationic current described in the preceding paper (Kehoe, 1990). The synaptic current elicited by these so-called “blocking” neurons was compared, in hyperpolarized medial cells, with the current induced by an intracellular injection of cAMP. It was found that (1) both currents show an outward rectification, (2) both currents are enhanced and prolonged by phosphodiesterase inhibitors (as well as by intracellular acidification of the postsynaptic neuron and by bath-applied caffeine), and (3) both currents react in the same way to changes in (Ca)0, showing a net enhancement when (Ca)0 is reduced and, conversely, a marked diminution when extracellular (Ca)0 is increased. The increase in amplitude of the slow synaptic current in low-Ca solutions and its decrease in high-Ca seawater are contrary to the changes that would be expected from the known effects of Ca on transmitter release at chemical synapses, revealing the overriding importance of the postsynaptic block by Ca. The data presented here strongly suggest that both the slow inward current and the diminutions in K conductance induced by the firing of the 3 blocking neurons are mediated by cAMP. Like the 2 cAMP-mediated diminutions in K conductance (Kehoe, 1985a, b), the cAMP-activated slow inward current, because of its atypical voltage dependence, both depolarizes the medial cell and causes an increase in its input resistance at resting potential. Consequently, the synaptically activated increase in cAMP prolongs the excitability of the medial cells for up to tens of seconds after the end of presynaptic firing.